Newly Digitized Database Reveals the Lives and Families of Forced Migrants from Finnish Karelia - John Loehr; Robert Lynch; Johanna Mappes; Tuomas Salmi; Jenni Pettay; Virpi Lummaa (Population Research Institute, 2022)
Studies on displaced persons often suffer from a lack of data on the long-term effects of forced migration. A register created during 1960s and published as a book series ‘Siirtokarjalaisten tie’ in 1970 documented the lives of individuals who fled the southern Karelian district of Finland after its first and second occupation by the Soviet Union in 1940 and 1944. To realize the potential value of these data for scientific research, we have recently scanned the register using optical character recognition (OCR) software, and developed proprietary computer code to extract these data. Here we outline the steps involved in the digitization process, and present an overview of the Migration Karelia (MiKARELIA) database now available to researchers. The digitized register contains over 160000 adults and a wide range of data on births, marriages, occupations and movements of these forced migrants, likely to be of interest to researchers across disciplines including demographers, anthropologists, evolutionary biologists, historians, economists and sociologists.